The Role of Personality Test Results as a Tool for Student Self-Understanding and Its Implications in Counseling - Nuramita, Nuramita; Farah, Rina; Zubaidah, Zubaidah; Nurfadila, Nurfadila; Asmawati, Asmawati; Zulfikar, Zulfikar (Darussalam: Journal of Psychology and Educational, 2025)
Self-understanding is one of the main keys for students to achieve academic success and personal development, especially during adolescence which is known as the phase of searching for identity. In the world of education, personality has an important role in shaping students' behavioral patterns, learning styles, and social interactions. One tool that can support students' self-understanding is a personality test. This article aims to discuss the role of personality test results as a means of students' self-understanding and its implications in guidance and counseling services at school.